Physicochemical properties and osteoclastogenesis for three premixed calcium silicate-based sealers post set - Camila Maria Peres de Rosatto; Gabriela Leite de Souza; Danilo Cassiano Ferraz; Marcelo José Barbosa Silva; Mario Tanomaru Filho; Camilla Christian Gomes Moura (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: Solubility, pH, ion release, cytotoxicity, and osteoclastogenesis inhibition in bone marrow-derived monocyte macrophages (BMMs) were evaluated in EndoSequence BC Sealer (END), Bio-C Sealer (BC), and Sealer Plus BC (SPBC). pH was determined after immersion of the sealers in deionized water (DW) and Minimum Essential Medium Alpha (α-MEM). Solubility was obtained by mass loss. Ion release was measured by using X-ray fluorescence spectroscopy (XRF). Cytotoxicity was evaluated by MTT assay. Inhibition of osteoclastogenesis was evaluated by tartrate-resistant acid phosphatase (TRAP). Data were analyzed using the t-test, ANOVA and Tukey/Dunnett's post-hoc tests (α = 0.05). END had the highest pH in DW (p < 0.05), and BC, in α-MEM (p < 0.05). Solubility in DW was the lowest for SPBC (p < 0.005). The highest calcium release was observed for BC in DW at 12 h (p < 0.05), and in α-MEM at 12 and 24 h (p < 0.05). The lowest toxicity was detected for END (p < 0.05). BC had the highest inhibitory effect on osteoclasts (p < 0.05). Overall, the highest solubility and pH values were found in DW. However, the calcium silicate-based sealer showed higher solubility than the ISO standards. Calcium release was the highest for BC. END showed the highest cell viability, and BC, the highest osteoclast inhibition.